Reward dan Punishment Dalam Kinerja Karyawan PT. Bank Sumut Unit Usaha Syariah - Muhammad Arif; Siti Mujiatun (Universitas Muhammadiyah Sumatera Utara, 2022)
The purpose of this research is to test and determine the effect of rewards on employee performance at PT. Bank of North Sumatra Sharia Business Unit, To test and determine the effect of punishment on employee performance at PT. Bank of North Sumatra Sharia Business Unit, To test and determine the effect of reward and punishment simultaneously on employee performance at PT. Bank of North Sumatra Sharia Business Unit.Research Methods This thesis is a type of quantitative research, with data collection techniques in the form of questionnaires, data collection techniques in the form of questionnaires distributed to 30 respondents. In analyzing the data, the researcher used multiple regression data analysis with several steps of data validity test, multiple linear regression test and hypothesis testing. The results of this study, showed the results of the t arithmetic value of 0.268 with a significant level of 0.791. This significant level is proven to be greater than 0.05, meaning that the reward has a significant effect on employee performance at PT. Bank of North Sumatra Sharia Business Unit, the value of t count is 0.048 with a significant level of 0.962. This significant level is proven to be greater than 0.05, meaning that the Punishment variable has a significant effect on employee performance at PT. Bank of North Sumatra Sharia Business Unit. In the simultaneous test (F test), it is known that F-count (2.005) F-table (3.35) and sig-p (0.000) 0.05, meaning that the Reward and Punishment variables simultaneously or jointly have a significant effect on employee performance at PT. Bank of North Sumatra Sharia Business Unit.